2007
DOI: 10.1007/s12016-007-0044-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of Bacterial Pathogens in Atopic Dermatitis

Abstract: The skin of atopic dermatitis (AD) patients exhibits a striking susceptibility to colonization and infection with Staphylococcus aureus. This review summarizes our understanding about the role of S. aureus in AD. Indeed, S. aureus colonization is both a cause and a consequence of allergic skin inflammation. The mechanisms that allergic skin inflammation of AD promotes the increase of S. aureus colonization include skin barrier dysfunction, increased synthesis of the extracellular matrix adhesins for S. aureus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 146 publications
(237 reference statements)
2
75
0
7
Order By: Relevance
“…According to the present state knowledge, S. aureus colonisation reaches 75 -100% in lesional skin of AD patients, and 30 -100% of AD patients have this bacteria in their nonlesional skin. By contrast, only 5 -30% of healthy people are carriers of S. aureus [5,14,15,16,17]. The results of this study were consistent with thethe above observations -S. aureus was isolated from the skin lesions of 81% of AD patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to the present state knowledge, S. aureus colonisation reaches 75 -100% in lesional skin of AD patients, and 30 -100% of AD patients have this bacteria in their nonlesional skin. By contrast, only 5 -30% of healthy people are carriers of S. aureus [5,14,15,16,17]. The results of this study were consistent with thethe above observations -S. aureus was isolated from the skin lesions of 81% of AD patients.…”
Section: Discussionsupporting
confidence: 92%
“…It is widely known that inflammation in the course of AD is stimulated by the antigens of skin-colonising microorganisms. Damage to the epidermal barrier facilitates their penetration into the epidermis and dermis [5]. Staphylococcus aureus (S. aureus) has a predominant role among the pathogens responsible for exacerbation of the dermatological condition in AD patients [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…S. aureus may also show enhanced adherence properties to skin cells, which has been shown when comparing atopic eczema sufferers with normal control subjects. 240,241 Other studies reviewed elsewhere 242,243 have suggested that the balance of pathogenic and synbiotic bacterial species on the skin is altered in atopic eczema, resulting in an agitated skin microbiome.…”
Section: Rationalementioning
confidence: 99%
“…Leung et al reported that S. aureus isolated from lesional skin of more than half of their patients with AD could secrete toxins with the characteristics of SAgs (13). The SAgs of S. aureus are composed of enterotoxins (SEA, SEB, SEC), exofoliative toxins (ETA, ETB), and TSST-1 (14). Furthermore, these SAgs trigger the immunologic responses mediated by cytokines, resulting in inflammation of tissues (6)(7)(8)15).…”
Section: Discussionmentioning
confidence: 99%